Efficacy of non-invasive intelligent volume assured pressure support (iVAPS) and pressure support ventilation (PSV) in clinical practice (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY Noninvasive ventilation (NIV) is a well-established treatment option for hypercapnic respiratory failure; however, the best mode of ventilation remains unknown. The aim of this retrospective study was to compare patients’ adherence to NIV using either pressure support ventilation (PSV) or intelligent volume-assured pressure support (iVAPS). PATIENTS AND METHODS In this retrospective cohort study, we assessed in- and outpatients suffering from hypercapnic respiratory failure of various aetiologies (chronic obstructive pulmonary disease [COPD], obese COPD [body mass index >30 kg/m2], obesity hypoventilation syndrome and other diseases such as amyotrophic lateral sclerosis or interstitial lung disease) after NIV initiation with PSV or iVAPS. Adherence to treatment was compared between these modes using the Wilcoxon test. Within-group differences were tested using linear regression models. Mortality and emergency hospital readmission rates were modelled using Kaplan-Meier estimates and Cox proportional hazards models. RESULTS Adherence to treatment was similar in both groups throughout the observation period – after 6 weeks: PSV 363 min/night (interquartile range [IQR] 200–448), iVAPS 369 min/night (IQR 310–468) (p = 0.619); after 1 year: PSV 423 (323–500), iVAPS 429 (298–475) (p = 0.901); at the last follow up: PSV 481 (395–586), iVAPS 426 (391–565) (p = 0.284). NIV reduced PaCO2 significantly compared with baseline at all follow-ups: PSV −1.29/−1.49/−1.49 kPa, iVAPS −1.47/−1.23/−1.24 kPa, p 4 h/night and >80% nightly usage) was associated with a lower mortality rate (HR 0.34, 95% CI 0.15–0.77; p = 0.010). CONCLUSION In a real-world setting of a mixed population with hypercapnic respiratory failure, iVAPS and PSV seem to be similarly effective in improving gas exchange and demonstrate excellent adherence to treatment. A longer survival was noted in NIV-adherent patients. Randomised controlled studies are necessary to identify patients who might benefit more from hybrid ventilation modes.